Walking indoors, walking outdoors: an fMRI study - Dalla Volta, Riccardo; Fasano, Fabrizio; Cerasa, Antonio; Mangone, Graziella; Quattrone, Aldo; Buccino, Giovanni (Frontiers in Psychology, 2015)
An observation/execution matching system for walking has not been assessed yet. The present fMRI study was aimed at assessing whether, as for object-directed actions, an observation/execution matching system is active for walking and whether the spatial context of walking (open or narrow space) recruits different neural correlates. Two experimental conditions were employed. In the execution condition, while being scanned, participants performed walking on a rolling cylinder located just outside the scanner. The same action was performed also while observing a video presenting either an open space (a country field) or a narrow space (a corridor). In the observation condition, participants observed a video presenting an individual walking on the same cylinder on which the actual action was executed, the open space video and the narrow space video, respectively. Results showed common bilateral activations in the dorsal premotor/supplementary motor areas and in the posterior parietal lobe for both execution and observation of walking, thus supporting a matching system for this action. Moreover, specific sectors of the occipital-temporal cortex and the middle temporal gyrus were consistently active when processing a narrow space versus an open one, thus suggesting their involvement in the visuo-motor transformation required when walking in a narrow space. We forward that the present findings may have implications for rehabilitation of gait and sport training.